2013
DOI: 10.1007/s11121-013-0370-1
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Lifestyle and Habits Questionnaire-Brief Version: Relationship to Quality of Life and Stress in College Students

Abstract: The authors describe the development and preliminary evaluation of the Lifestyle and Habits Questionnaire-brief version (LHQ-B). Three hundred seventy-seven undergraduate students (ages 18-25) participated. Responses were collected through either a web-based or face-to-face survey. Data reductive procedures were used with a preexisting lifestyle inventory to create an abbreviated measure. The relationship between lifestyle domains and indicators of wellbeing (levels of stress and quality of life (QOL)) were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
0
23
0
2
Order By: Relevance
“…This question is associated with a negative score, and the percentage of girls who do not eat breakfast daily is greater than that of boys. The study by Dinzeo et al in 2013 [ 61 ] amongst 18- to 25-year-old individuals evaluates cholesterol, sugar, sodium, fruit, and vegetable intake. In the study, as in the VISA-TEEN, girls have higher scores than boys do.…”
Section: Discussionmentioning
confidence: 99%
“…This question is associated with a negative score, and the percentage of girls who do not eat breakfast daily is greater than that of boys. The study by Dinzeo et al in 2013 [ 61 ] amongst 18- to 25-year-old individuals evaluates cholesterol, sugar, sodium, fruit, and vegetable intake. In the study, as in the VISA-TEEN, girls have higher scores than boys do.…”
Section: Discussionmentioning
confidence: 99%
“…With an adjustment in flexibility in scheduling of academic courses and rise/wake times, college students are also confronted with making decisions regarding their physical activity (Dinzeo et al, 2014). Beginning college is often associated with weight gain; however, research has found that with an increase in physical activity, college students have reported an increase in weight loss (Gropper et al, 2012).…”
Section: Sleep and Physical Healthmentioning
confidence: 99%
“…Factors associated with a college student's lifestyle may provide an environment leading to poor sleep quality. With the adjustment to college, students are confronted with lifestyle factors associated with such adjustment including deciding the contents of a meal, sleep routines, the level of physical activity in which to engage, and alcohol and substance use (Dinzeo, Thayasivam, & Sledjeski, 2014).…”
Section: Sleep and Physical Healthmentioning
confidence: 99%
“…To measure participants' agreement with engaging in various health behaviors, we used a 28-item measure of health behaviors that included 14 unambiguous items measuring behaviors with clear implications for health, and 14 ambiguous items measuring behaviors that lacked clear implications for health. The unambiguous items were selected from the Lifestyle and Habits Questionnaire-Brief Version (LHQ-B; Dinzeo, Thayasivam, & Sledjeski, 2014), which is a 42-item survey designed to assess health-related attitudes and behaviors in a variety of lifestyle domains (e.g., health and exercise, social concern, nutrition). We operationalized unambiguous as having clear implications for health, considering that guidelines and recommendations abound regarding alcohol, fruit, or water consumption, and other behaviors such as exercise and substance use.…”
Section: Health Assessmentmentioning
confidence: 99%